Investigation of catalytic activity of solid acidic Fecl3/bentonite catalyst on the synthesis of some (E)-1-(2, 4-dimethylthiazol-5-yl)-3-phenylprop-2-en-1-ones by solvent-free technique. (2020) - Balaji, S.; Manikandan, V.; Rajarajan, M.; Usha, V.; Rajalakshmi, S.; Venkatachalam, P.; Muthuvel, I.; Thirunarayanan, G.
Abstract: In this work, an attempt was made to synthesized more than 90% yields of ( E )-1-(2, 4-dimethylthiazol-5-yl)-3-phenylprop-2-en-1-one by cross-aldol condensation reaction of 5′acetyl 2, 4-dimethylthiazole with various substituted benzaldehydes in the presence solid acidic FeCl3 /Bentonite catalyst using microwave irradiation under solvent-free conditions. The synthesized ( E )-1-(2, 4-dimethylthiazol-5-yl)-3-phenylprop-2-en-1-one derivative was characterized by physical constants, UV, FT-IR, 1 H NMR and 13 C NMR spectral data. In this condensation, the effect of catalytic activity was investigated by the obtained yield of enones and reusability. This greener technique offered for high yield of 2, 4-dimethylthiazole enones.